Bipolar loop device versus bipolar diathermy for tonsillectomy: A pilot randomized controlled trial. (February 2021) - Fakhrealizadeh, Fatemeh; Hoveidaei, Amir Human; Eslami, Jamshid; Hashemi, Seyed Basir; Hoveidaei, Armin; Kazemi, Tayebeh; Nazarpour, Zohre
Abstract: Objective: Tonsillectomy is one of the most common surgeries performed in the pediatric population. Although different forms of instruments and various methods are used to perform tonsillectomy, none of them is still recognized as the best global technique. This study aimed to compare the outcomes of the new Bipolar Loop tonsillectomy versus bipolar diathermy technique. Methods: This study is a pilot randomized clinical trial and was conducted on 40 pediatric patients who were the candidate of tonsillectomy. Patients were divided into two groups of Bipolar Loop or bipolar diathermy. Operation time, intraoperative bleeding, tonsillar fossa wound, postoperative complications, and duration of return to normal diet were evaluated in the current study. Results: In both of the Bipolar Loop and bipolar diathermy groups, no significant difference was found in terms of sex, age, and weight. The average amount of the operative time, intra-operative blood loss, and postoperative pain loss were significantly less in the Bipolar Loop group (P < .001). In addition, the tonsillar fossa wound healing scores were significantly better (on the 14th day, P = 0.009). However, there was no significant difference between the two groups in terms of postoperative bleeding, duration of return to a normal diet, and postoperative symptoms of fever, otalgia, or voice change between the groups. Conclusion: The study showed that blood loss and postoperative pain through day 7 were significantly less in the Bipolar Loop group. Tonsillectomy with Bipolar Loop can be recommended as one of the methods for tonsillectomy, especially in pediatric patients.